Climate change acknowledgement and responses of summer (glacier) ski visitors in Norway. Issue 4 (2nd October 2018) - Demiroglu, O. Cenk; Dannevig, Halvor; Aall, Carlo
ABSTRACT: The mutual interaction of climate change and the highly weather-dependent ski tourism business is drawing increasing attention from the academic, commercial and political arenas. Changes in the cryosphere are becoming major determinants of the sustainability of ski areas. Therefore, there is a great deal of literature entailing impact and adaptation studies regarding ski areas, resorts, and destinations; however, research on the demand side of the issue is relatively limited. In this paper, the relationship between climate change and a niche segment of ski tourism, summer skiing, is discussed with regard to the awareness, perceptions, and mitigation and substitution behaviours of visitors to the summer downhill ski centres in Norway – an underresearched country, despite its recognition as the cradle of skiing. For this purpose, a comprehensive survey was administered to a sample of 224 subjects. The results revealed high climate change awareness but limited climate friendliness, and a strong emphasis on the immediate climate impacts on summer skiing that create a tendency towards ski activity substitution within Norway. Individual profiles also played a significant role in the anticipated mitigation and substitution behaviours. The implications of the results involving demand attitude and behaviour are further discussed with regard to the suppliers.